A Hoard of Russian Coins of the 18th Century from the Village of Emylivka (Holovanivsky District of Kirovohrad Region) - Bondarenko, Olexander; Kapeliushnyi, Valerii; Tupchiyenko, Mykola; Shvets, Dmytro (Acta Archaeologica Lodziensia, 2021)
In the spring of 2020 in the vicinity of the village Yemylivka (Golovanivskyi district, Kirovohrad region) local residents carrying out agricultural work accidentally discovered a hoard placed in a clay pot (Fig. 1). The deposit comprised coins which were in circulation in the Russian Empire during the XVIII century. The vast majority of the coins in the hoard are large-format copper 5 kopeck coins amounting to 40 pieces, as well as two silver rubles. Accordingly, the total value of the deposit is 4 rubles. The oldest coin of the complex is a ruble of 1731, and the youngest a 5 kopeck piece of 1786. The presence in this coin deposit of the XVIII century of only 2 silver rubles, minted in the 1730s, indicates the insignificant presence of large denomination silver coins in the money market of southern Ukrainian lands on the border with the Polish-Lithuanian Commonwealth in the last quarter of the XVIII century. This is due to the monetary policy of the Russian authorities in Ukraine, relating to a ban on the export of silver coins outside the empire. This hoard of Russian coins of the XVIII century, which has already been the object of scientific attention, has several interesting features, in particular the presence in the hoard of two silver ruble coins, which furthermore are previously undescribed varieties. This hoard expands the our knowledge about the circulation of money in the Southern Ukraine in the XVIII century, especially in the lands bordering the Polish-Lithuanian Commonwealth.